MORPHOLOGICAL AND ANATOMICAL RESEARCH OF ONOSMA CAUCASICUM LEVIN.EX M.POP OF BORAGINACEAE JUSS FAMILY - F. K. Serebryanaya (Фармация и фармакология (Пятигорск))
The micromorphological and anatomical properties of Onosma caucasicum Levin.ex m.Pop. were investigated. O. caucasica is an endemic species. Epidermal cells containing crystal needles were observed in O. caucasica. Studied Onosma species had isobilateral type of leaves. Stomata were anisocytic and anomocytic. Glandular and eglandular trichomes especially porrect-stellate and simple trichomes were densely seen on the both upper and lower epidermis of leaves in two species.